Pengaruh Kepuasan Kerja Terhadap Motivasi Kerja dan Dampaknya Terhadap Kinerja Guru SMK Pasca Covid-19 di Aceh Timur - Jamali Jamali; Teuku Muana Refi (Jurnal EMT KITA, 2022)
The purpose of this study was to determine: (1) The effect of job satisfaction on work motivation, (2) The effect of job satisfaction on performance (3) The effect of job satisfaction on the performance of post-covid 19 vocational high school teachers in Aceh Regency. The data collection method in this research is survey, non-probability method with purposive sampling technique, which means that the sample is selected based on its characteristics, the data analysis tool uses SPSS with a sample of 120 respondents. The results of the analysis show that 1. there is no effect of job satisfaction on teacher work motivation, this is seen from the probability (sig) = 0.195 because the value of sig < 0.05 the correlation coefficient is not significant and the t-table is greater than t-count, it can be seen that work motivation is not influenced by job satisfaction, 2 there is an effect of job satisfaction There is teacher performance and 3 there is an impact of work motivation on teacher performance job satisfaction on the performance of post-covid 19 vocational high school teachers in East Aceh Regency.